A novel reciprocating cluster magnetorheological polishing device: Design and investigation of removal model. (July 2023) - Lu, Mingming; Zhuang, Xulong; Zhou, Jiakang; Lin, Jieqiong; Li, Weixing
In the traditional magnetorheological polishing of flat planar elements, there have been problems like low efficiency and uneven surface. To improve the surface quality of optical glass and explore the material removal mechanism, a novel reciprocating cluster magnetorheological polishing (MRP) device was designed with a magnetic field consisting of six curved permanent magnets and one static magnetic finite element for analysis. By analyzing the forces and motion behaviors of single abrasive particles during the polishing process, a novel removal model was developed and the effects of the main parameters on the material removal mechanism were investigated. The experiments ware conducted on the K9 glass through the polishing process by this proposed device and traditional cold working separately. The results showed that reciprocating cluster MRP for 120 min was able to achieve a surface roughness of 2.7 nm, a Peak to Valley (PV) value of 0.689 fr (216 nm) and a Root Mean Square (RMS) value of 0.077 fr (24 nm), respectively, which made a significant improvement on the conventional cold working. Therefore, the proposed device and novel polishing process could effectively reduce the surface roughness value and the PV value of K9 glass, while improving both the polishing efficiency and accuracy of optical components.